Public-Private Partnership in the Sphere of Conservation of Cultural Heritage Objects: Legal Security and Economic Efficiency (On the Example of F.N. Plevako’s Manor Located in the Village of Vishnevoe in Staroyuryevsky District in Tambov Region) - Yana Yu. Radyukova; Adamov Ernest Valeryevich; Dorozhkina Natalia Igorevna; Makareva Elena Afanasyevna (Communications of International Proceedings, 2020)
Description of a main objective of research. In 2018, the population of Tambov region began to show much more interest in cultural services and cultural objects. About 12.2 million people visited cultural institutions and took part in cultural events in 2018, which was 7.0% more than in 2017. The authors of the study made an attempt to develop a mechanism of interaction between the state and private investors to conserve cultural objects. The researchers proposed the measures to preserve the manor of the famous Russian lawyer F.N. Plevako which is a cultural heritage site of regional significance. Apart from that, the authors gave some recommendations on how to stimulate state bodies and private investors to develop mutually beneficial cooperation and preserve the historical heritage. Short description of methodology. The authors of the study used the following methods: analysis, synthesis, deduction, induction and classification. In addition, the researchers applied such methods as desk research, study of documentation, description and modeling. Compilation of the most important research results and their significance. The research is practically oriented as it contributes to the restoration of F.N. Plevako’s manor located in the village of Vishnevoe in Staroyuryevsky district in Tambov region. The authors determined the market value in accordance with the Federal Valuation Standards and calculated the total amount of investments for the reconstruction of the estate. The financial model of the return on investment was developed in accordance with the methodological recommendations proposed by the Ministry of Economic Development (recommendations for the implementation of PPP projects).
Keywords: public-private partnership; cultural heritage objects; concession agreement; concessionaire; concessioner.